Implementasi Penilaian Diri Siswa dalam Pembelajaran Matematika Berbasis Cooperative Learning Tipe STAD Pada Siswa Kelas VIII SMP Muhammadiyah 1 Sukoharjo Tahun Ajaran 2016/2017 - Herliani, Elis Fitria, Drs. Sumardi,M.Si (2017)
This study aimed to describe the understanding teacher at SMP Muhammadiyah 1 Sukoharjo on student self-assessment, describing the implementation of self-assessment of students in mathematics-based cooperative learning STAD, describing the obstacles in the learning of mathematics-based cooperative learning type STAD with student self-assessment. Based on this research approach is qualitative descriptive study. This research subject is class VIIID SMP Muhammadiyah 1 Sukoharjo totaling 25 students. data collection techniques using questionnaires, observai, tests, interviews, and documentation. Data validation was done by triangulation technique by comparing the data results of the questionnaire, observai, tests, interviews, and documentation. Data analysis technique is done by means of data reduction, data presentation, and verification of data and drawing conclusions. Based on the research we concluded that: (1) teacher at SMP Muhammadiyah 1 Sukoharjo already know about the self-assessment but not yet apply to students optimally (2) the results of completeness at the first meeting by 36% (8 students) with an average marginal 70 and self assessment percentage of 50% (11 students) obtain criteria Very Good (SB), 32% (7 students) obtain criteria Good (B), and 18% (4 students) gain criterion Enough (C). The second meeting by 61% (11 students) with an average marginal 77 and the percentage of Penialain themselves 50% (9 students) obtain criteria Very Good (SB), 33% (6 students) obtain criteria Good (B), and 17% ( 3 students) gain criterion Enough (C). at the third meeting of 37% (9 students) with an average marginal 68 and the percentage of Penialain themselves 54% (13 students) obtain criteria Very Good (SB), 29% (7 students) obtain criteria Good (B), and 17% (4 students) gain criterion Enough (C) (3) obstacles encountered in the study is that students do not pay attention to the explanation the researchers, the lack of enthusiasm of students, The valuation technique used is a new thing for students.